Implications of Conditional Inconstitutional Decisions in The Constitutional Court Decision: Implikasi Putusan Inkonstitusional Bersyarat dalam Putusan Mahkamah Konstitusi - Irna Nurhayati; Aminoto Aminoto (Jurnal Konstitusi, 2023)
This research focuses on the decision of Constitutional Court Number 91/PUU-XVIII/2020, which states that Law Number 11 of 2020 concerning Job Creation is unconstitutional because of a formal flaw in its formation. This study aims to answer two questions. First, regarding the development and characteristics of conditional decisions issued by the Constitutional Court. Second, what are the implications of conditional unconstitutional decisions issued by the Constitutional Court in Decision Number 91/PUU-XVIII/2020? The research method used is doctrinal legal research with a secondary database. The research results show; (1) there are two types of conditional decisions at the Constitutional Court: conditional constitutional decisions and conditional unconstitutional decisions. (2) Decision Number 91/PUU-XVIII/2020 can potentially cause an ambiguous interpretation regarding conditional unconstitutionality because the Constitutional Court, in its a quo decision, stated that Law Number 11 of 2020 concerning Job Creation remains valid. When referring to the conditional unconstitutional meaning generally understood, the law should be unconstitutional until the amendments are completed.